The Influence of Spiritual Intelligence, Financial Knowledge, and Self-Control on Financial Behavior with Self-Efficacy Moderation on Students of Ma'had Sunan Ampel Al-'Aly - Putri Setia Septaviani; Farahiyah Sartika (Jurnal Ecogen, 2026)
Research examining the influence of spiritual intelligence, financial knowledge, and self-control on financial behavior, with self-efficacy as a moderating variable, in the context of Islamic boarding school students (mahasantri) remains limited, as most previous studies have focused on general university students. Therefore, this study aims to analyze the relationship between spiritual intelligence, financial knowledge, and self-control and the financial behavior of students at Ma'had Sunan Ampel Al-'Aly UIN Malang, as well as to examine the moderating role of self-efficacy. This study employs a quantitative approach using PLS-SEM and involves 98 respondents selected through the Slovin formula. The results indicate that spiritual intelligence and financial knowledge have a positive and significant effect on financial behavior, while self-control does not have a significant effect. The findings also reveal that self-efficacy moderates the relationship between spiritual intelligence and financial knowledge and financial behavior, but does not moderate the relationship between self-control and financial behavior. The structural model explains 85% of the variance in financial behaviour (R² = 0.850). These findings contribute to the development of behavioral finance literature by highlighting the role of spiritual, cognitive, and psychological factors in shaping the financial behavior of Islamic boarding school students and underscore the importance of strengthening these factors to promote responsible financial behavior within Islamic educational environments.